Sport Development Strategy for Rock Climbing at Central Bengkulu Regency - Prabowo, Andika; Raibowo, Septian; Nopiyanto, Yahya Eko; Permadi, Andes; Rizky, Oddie Bernanda (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
This study aimed to formulate a sports development strategy for rock climbing on the Kandis Hills in central Bengkulu. A descriptive qualitative approach was used in the design of this study. This research began with the identification and analysis of the disease's internal environment (strengths and weaknesses) and formative external environment (opportunities and threats). This study used his SWOT analysis with IFAS and EFAS matrices. The instruments of this study were interviews, observations, questionnaires, and documents. The study sample consisted of 2 individuals from interview data collection and observation by subject sampling techniques and 30 respondents from a questionnaire. As a result of the study based on SWOT analysis, the researchers found that tourism sport climbing cliffs on Kandice Hill in quadrant I had an internal factor value of +0.4 and an external factor value of +0.68 in the SO strategy (between external and external factors). I discovered something. Internal Opportunities) Sport Climbing Tourism's strategic location in Bukit Kandis provides opportunities and strengths to maximize existing opportunities.